Conflict and the Nature of Precautionary Wealth - Aghabarari, Leila (World Bank, Washington, DC, 2018)
The paper uses a detailed household survey to document precautionary wealth accumulation in Afghanistan, with wealth being significantly higher for households facing higher income uncertainty. Annual household expenditure on nondurable goods is also lower for these households. There is no significant difference in the wealth response to income uncertainty across high- and low-conflict provinces. However, the constituents of precautionary wealth vary drastically. While households in the low-conflict regions rely almost exclusively on livestock to iron out uncertainty, households in the high-conflict areas also build up a reserve of gold and silver. This shift in household portfolio suggests a more substantial decline in real returns of livestock relative to jewelry in high-conflict provinces.